Model for evaluating teacher and trainer competences - Carioca, Vito [Verfasser]; Rodrigues, Clara [Verfasser]; Saúde, Sandra [Verfasser] (My University, 2009)
"A lack of common criteria for comparing education and training systems makes it difficult to recognise qualifications and competences acquired in different environments and levels of training. A valid basis for defining a framework for evaluating professional performance in European educational and training contexts must therefore be established. In this context, the TEVAL project presents a proposal for an evaluation model applied to teaching and training competences. The model is based on a common competence framework and on a holistic concept of the theoretical principles that justify the evaluation process, bearing in mind professional development and system regulation - the Close Evaluation Model." TEVAL was developed (2005-2007) by a partnership of expert evaluation institutions from six European countries: the Instituto Politécnico de Beja/Escola Superior de Educação de Beja (Scientific Coordinator of the Project) (Portugal), Univation Institute (Germany), EntenteUK (United Kingdom), Centre International d'Études Pédagogiques (France), Tallinn University (Estonia) and the Hellenic Regional Development Centre (Greece). (Autorenreferat, BIBB-Doku)
Keywords: L 6.3.1 Diagnose- & Messinstrumente; P 3.2.3 Lehrer; P 3.2.1 Ausbilder; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; Arbeitsleistung; Leistungsfähigkeit; Kompetenzentwicklung; Kompetenzprofil; Kompetenzbewertung; Lehrer; Ausbilder; Evaluation; EU-Programm; LEONARDO